Difference between general and specific swimming abilities of junior top water polo players based on their position within the team - Bratusa, Z.; Dopsaj, M. (Biomechanics and Medicine in Swimming X, 2006)
Tactical, technical and functional demands of each position during game are a very significant factor for planning the training. The basic aim of this paper was to define the differences in basic and specific swimming characteristics of junior water polo players based on their position within the team. The sample of 31 players was divided into three groups: 1. players in wing positions (N = 19); 2. centers (N = 6); 3. backs (N = 6). 12 variables were the result of the following swimming tests: crawl 25m, 50m and 1500m, 25m crawl with ball, 25m back, specific swimming using legs 25m, legs crawl, breast and mixing and swimming 10x50m crawl. Cluster analysis has singled out five variables in which the observed groups differed. After the Student T-test, we obtained the difference between the groups. The players in wing positions are weaker then the others and that is not suitable for game.